Biofabrication of cell-laden allografts of goat urinary bladder scaffold for organ reconstruction/regeneration. (December 2020) - Vishwakarma, Sandeep Kumar; Sarwar, Shahana; Adil, Mohammed Abdul Majid; Khan, Aleem Ahmed
Graphical abstract: Highlights: The study highlights use of urinary bladder from goat to prepare suitable scaffolds. Widely acceptable cell source has been demonstrated for biofabrication. DUB scaffolds provides required biological and mechanical support for cells. Cell-laden allografts could be suitable choice for organ regeneration. Use of human UCS provides xeno-free graft for clinical applications. Abstract: Introduction: Bladder dysfunction has been considered as one of the most critical health conditions with no proper treatment. Current therapeutic approaches including enterocystoplasty have several limitations. Hence, biofabrication of cell-laden biological allografts using decellularized Goat urinary bladder scaffolds for organ reconstruction/regeneration was major objective of this study. Materials and methods: An efficient method for decellularization of Goat urinary bladder (N = 3) was developed by perfusion of gradient change of detergents through ureter. The retention of organ architecture, extracellular matrix composition, mechanical properties and removal of cellular components was characterized using histological, cellular and molecular analysis. Further, mesenchymal stem cells (MSCs) from human umbilical cord blood (UCB) were used for preparing biological construct of decellularized urinary bladder (DUB) scaffolds to augment the urinary bladder reconstruction/regeneration. Results: The decellularization method adopted in this study generated completely DUB scaffolds within 10 h at 100 mm Hg pressure and constant flow rate of 1 mL/min. The DUB scaffold retains organ architecture, ECM composition, and mechanical strength. No significant amount of residual nucleic acid was observed post-decellularization. Furthermore, MSCs derived from human UCB engrafted and proliferated well on DUB scaffolds in highly aligned manner under xeno-free condition. Conclusion: Biofabricated humanized urinary bladder constructs provides xeno-free allografts for future application in augmenting urinary bladder reconstruction/regeneration with further development.